Governing dynamics and preferential binding of the AXH domain influence the aggregation pathway of Ataxin‐1. Issue 3 (19th October 2022) - Tammara, Vaishnavi; Das, Atanu
Abstract: The present state of understanding the mechanism of Spinocerebellar Ataxia‐1, a fatal neurodegenerative disease linked to the protein Ataxin‐1 (ATXN1), is baffled by a set of self‐contradictory, and hence, inconclusive observations. This fallacy poses a bottleneck to the effective designing of curable drugs as the field is currently missing the specific druggable site. To understand the fundamentals of pathogenesis, we tried to decipher the intricacies of the extremely complicated landscape by targeting the relevant species that supposedly dictate the structure–function paradigm. The atomic‐level description and characterization of the dynamism of the systems reveal the existence of structural polymorphism in all the leading stakeholders of the overall system. The very existence of conformational heterogeneity in every species creates numerous possible combinations of favorable interactions because of the variability in segmental cross‐talks and hence claims its role in the choice of routes between functional activity and dysfunctional disease‐causing aggregation. Despite this emergent configurational diversity, there is a common mode of operative intermolecular forces that dictates the extent of stability of all the multimeric complexes due to the localized population of a specific type of residue. The present research proposes a dynamic switch mechanism between aggregability and functional activity, based on the logical interpretation of the estimated variables, which is practically dictated by the effective concentration of the interacting species involved in the cell.